ANALISIS REAKSI INVESTOR TERHADAP PENGUMUMAN RIGHT ISSUE DI BURSA EFEK INDONESIA (BEI) - Eva Zulaikha; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study was conducted with the aim of analyzing investor reactions, to the announcement regarding rights issue, for companies that carry out rights issues in 2018 with five days upon to the date of rights issue and five days after the date of rights issue, the variabels used in this study are abnormal returns and trading volume activities. The sample used in this study was 26 companies that carried out rights issues in 2018 with the study period, wich was five days before the rights issue and five days after the right issue, based on the test results using wilcoxon sagned rank test showed that there was no differences in TVA and abnormal returns before and after the issuance of rights.